Acidophilic bioleaching at high dissolved organic compounds: Inhibition and strategies to counteract this - Vardanyan, Arevik; Vyrides, Ioannis (My University, 2019)
Bioleaching is an efficient environmentally safe process for extracting metals from ore and waste sludge. In the bioleaching/biohydrometallurgical process, mainly chemolithotrophic microorganisms convert insoluble metal sulphides or oxides (directly or indirectly) into water-soluble metals. However, the presence of high dissolved organic compounds (DOCs) can severely decrease the activity of acidophilic bioleaching microorganisms. The DOCs can be generated through cell lysis or can be entrapped in heap ore bioleaching through the solvent extraction. Besides, in case of waste sludge bioleaching the high DOCs from organic sludge may hinder the activity of chemolithotrophic microbes. Therefore, this review critically discusses: (a) the effect of DOCs on the acidophilic chemolithotrophic microorganisms; (b) the effect of co-inoculation of acidophilic chemolithotrophic microorganisms and acidophilic heterotrophic bacteria; (c) the effect of DOCs from solvent extraction to acidophilic chemolithotrophic microorganisms and strategies to alleviate this and (d) the effect of DOCs on acidophilic sludge bioleaching and the positive co-inoculation with acidotolerant yeast.
Keywords: Bioleaching; Acidophilic chemolithotrophic microorganisms; High dissolved organic compounds (DOCs); Solvent extraction; Sludge